2020
DOI: 10.1177/0022034520903725
|View full text |Cite
|
Sign up to set email alerts
|

Examining Bias and Reporting in Oral Health Prediction Modeling Studies

Abstract: Recent efforts to improve the reliability and efficiency of scientific research have caught the attention of researchers conducting prediction modeling studies (PMSs). Use of prediction models in oral health has become more common over the past decades for predicting the risk of diseases and treatment outcomes. Risk of bias and insufficient reporting present challenges to the reproducibility and implementation of these models. A recent tool for bias assessment and a reporting guideline—PROBAST (Prediction Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Even though this analysis related to a special segment of prediction studies, our finding of inadequate reporting in the field of melanoma risk prediction is comparable to other studies [ 64 , 65 , 66 , 67 ]. Heus et al [ 65 ] included 146 publications across 37 clinical domains and reported a median TRIPOD adherence of 44%, which is even lower than the median of the studies included in our analysis (57%).…”
Section: Discussionsupporting
confidence: 82%
“…Even though this analysis related to a special segment of prediction studies, our finding of inadequate reporting in the field of melanoma risk prediction is comparable to other studies [ 64 , 65 , 66 , 67 ]. Heus et al [ 65 ] included 146 publications across 37 clinical domains and reported a median TRIPOD adherence of 44%, which is even lower than the median of the studies included in our analysis (57%).…”
Section: Discussionsupporting
confidence: 82%
“…Of note in the studies of other diseases consulted 13,59‐63 was that analysis was the domain that presented the greatest risk of bias, as in various reviews either no or very few studies among those included did this correctly. The other domains, however, both for risk of bias and applicability, were quite satisfactory, surpassing 70% in almost all the reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 articles included, only one had eight questions assessed positively (the article failed to indicate how it handled missing data, unclear), 48 another had seven questions assessed satisfactorily while the other two were negative (missing data from combining the missing data with the reference category and using univariate analysis to select the model predictors), 58 and three articles had six positive ques- did not adequately handle continuous predictors, used univariate analysis to select model predictors and we could not assess missing data 54 and (3) Lagu et al (2011): did not take into account overfitting, and there were two items for which we had no information for their assessment, the first being missing data and the second the questionable use of all patients to develop the model since when making exclusions after starting the follow-up, this was unclear. 57 Of note in the studies of other diseases consulted 13,[59][60][61][62][63] was that analysis was the domain that presented the greatest risk of bias, as in various reviews either no or very few studies among those included did this correctly. The other domains, however, both for risk of bias and applicability, were quite satisfactory, surpassing 70% in almost all the reviews.…”
Section: References Discrimination (Auc With 95% Ci) Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…These clinical decision support tools are all developed based on clinical prediction modelling research, which aims to yield the most accurate outcome prediction by capturing patterns in the available data (known as data-generating mechanisms) and minimizing the difference between the predicted and observed outcome (known as bias). However, following the up-to-date bias assessment criteria (PROBAST-Prediction model Risk Of Bias ASsessment Tool) [ 6 ] and reporting guidelines (TRIPOD-Transparent Reporting of a multivariable prediction model for Individual Prognosis or Diagnosis) [ 7 ], the overall quality of oral health prediction modelling studies was found to be less than optimal due to the presence of multiple sources of bias (e.g., measurement error, unmeasured predictors) and lack of reporting transparency [ 8 ].…”
Section: Introductionmentioning
confidence: 99%